PERLINDUNGAN HUKUM TERHADAP NASABAH DALAM TRANSAKSI KEUANGAN SYARIAH DI INDONESIA - Gaffar, Azis; Adryan, Muhammad (Jurnal Al-Kharaj: Studi Ekonomi Syariah, Muamalah, dan Hukum Ekonomi, 2026)
The development of the Islamic finance industry in Indonesia necessitates effective legal protection for customers, as they tend to occupy a weaker position in contractual relationships with Islamic financial institutions. Such legal protection is derived not only from national regulations but also from Islamic legal principles that emphasize justice, balance, and public welfare (maslahah). In practice, customer protection continues to face various challenges, particularly information asymmetry, the use of standardized contracts, and customers’ limited understanding of the legal consequences of the agreed-upon contracts. This study aims to analyze the legal position of customers in Islamic financial transactions, examine the implementation of customer legal protection within the national regulatory framework, and formulate an ideal concept of customer legal protection. This research employs a normative legal method with statutory and conceptual approaches. The findings indicate that although the existing regulatory framework provides a legal basis for customer protection, its implementation remains formalistic and suboptimal. Therefore, strengthening contractual transparency, balancing the bargaining positions of the parties, enhancing supervisory effectiveness, and improving legal and Islamic financial literacy are necessary to achieve fair and effective legal protection for customers.